About the Genesis of Pumice Deposits in the Region of Tarbagania and Pemzovaya Mountains in Kamchatka - O M Topchieva; T V Mostovaya; V A Petrovsky (Вестник Пермского университета. Геология, 2014)
This paper discusses the results of study of pumice deposits between volcanoes Gorely and Mutnovskiy on Kamchatka. A scheme of the pumice sheets is presented. The results of petrochemical and geochemical studies of pumice and acidic lavas of Mutnovsky and Gorely are discussed. A number of petrogeochemical pumice features indicating their possible genetic isolation is revealed.